Management of very early medical abortion—An international survey among providers. (March 2020) - Fiala, Christian; Bombas, Teresa; Parachini, Mirella; Agostini, Aubert; Lertxundi, Roberto; Lubusky, Marek; Saya, Laurence; Danielsson, Kristina Gemzell
Abstract: Objective: To record the definition and management of Very Early Medical Abortion (VEMA) in different countries. Study design: An Internet survey was circulated internationally among providers of medical abortion via a website. The questionnaire focused on reasons for performing or delaying medical abortion at a very early gestational age and the perceived advantages and disadvantages of VEMA. Results: Out of 220 completed questionnaires, 50 % came from European abortion providers (n = 110). Most respondents (72 %) defined VEMA as abortion performed in the presence of a positive hCG pregnancy test but with an empty uterine cavity or a gestational sac-like structure, and no signs or symptoms of ectopic pregnancy. A total of 74 % of respondents thought it was not necessary to wait for a diagnosis of intrauterine pregnancy before starting medical abortion. Equally, 74 % were aware of the possibility of an ectopic pregnancy. Conclusion: According to European providers of medical abortion, waiting for the diagnosis of an intrauterine pregnancy is not necessary and does not improve treatment of ectopic pregnancy. Providers should know that medical abortion can be performed effectively and safely as soon as the woman has decided. There is no lower gestational age limit.